2021
DOI: 10.2196/29126
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Mental Workload Associated With Digital Health Technologies in Health Care: Protocol for a Systematic Review Focusing on Assessment Methods

Abstract: Background The workload in health care is high; physicians and nurses report high stress levels due to a demanding environment where they often have to perform multiple tasks simultaneously. As a result, mental health issues among health care professionals (HCPs) are on the rise and the prevalence of errors in their daily tasks could increase. Processes of demographic change are partly responsible for even higher stress levels among HCPs. The digitization of patient care is intended to counteract t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Second, usability and acceptability assessment provided HCWs with an opportunity to identify several 2wT challenges. First, although 2wT will likely help prevent clients from being traced and reduce wasted tracing efforts, at scale 2wT could still increase workload as other digital technologies studies reported [19,48-49]. Responding to clients via SMS interactions, timely identification of more defaulters, and more clients identified for tracing could create need for additional support staff to help 2wT expand.…”
Section: Discussionmentioning
confidence: 99%
“…Second, usability and acceptability assessment provided HCWs with an opportunity to identify several 2wT challenges. First, although 2wT will likely help prevent clients from being traced and reduce wasted tracing efforts, at scale 2wT could still increase workload as other digital technologies studies reported [19,48-49]. Responding to clients via SMS interactions, timely identification of more defaulters, and more clients identified for tracing could create need for additional support staff to help 2wT expand.…”
Section: Discussionmentioning
confidence: 99%
“…However, impact of digital interventions on healthcare professionals' workload and efficiency is still an emerging topic of research. 28,29 Pharmacists generally had positive perceptions of compatibility and fit with organization goals, which are important facilitators of future SBI implementation. SBI components and its implementation format will need to be adapted for different pharmacies to ensure maximum compatibility, which also relates to the high adaptability of the SBI model.…”
Section: Discussionmentioning
confidence: 99%
“…However, impact of digital interventions on healthcare professionals’ workload and efficiency is still an emerging topic of research. 28,29…”
Section: Discussionmentioning
confidence: 99%
“…In a first step, all main characteristics of each study were extracted (study design, the setting of the target population such as a hospital, sample size, age, sex, and population type such as physicians). We only included studies with a sample size of under 20 participants provided that the risk of bias was adequate [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Contrary to what was defined in the protocol to this review, research questions 1.1 and 1.2 were not substituted to this final paper [ 32 ]. Deviating from the protocol’s attempt, we decided to use a different assessment tool to evaluate the risk of bias (QualSyst, [ 31 ]).…”
Section: Methodsmentioning
confidence: 99%